Catch them if you can?!: Angebote zur psychosozialen Unterstützung von Vätern mit Säuglingen und Kleinkindern unter besonderer Berücksichtigung der Teilnahmemotivation - Eickhorst, Andreas; Nakhla, Daniel; Schwinn, Lisa (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2010)
Programs with Psycho-Social Support for Fathers of Infants and Toddlers with Special Regard to Their Participation Motivation This paper shows different public and home based programs for fathers before and after the birth of a child. Some of the programs are part of general educational programs for parents; others are more gender-specific or focused on families within special contexts. The article's main focus is on the fathers' motivation to participate in such programs. What are the structural, but also the intrapersonal obstacles and barriers? Underlying assumptions about the consequences of non-participation are critically considered. In conclusion, possibilities to better attract fathers to participate in programs supporting them during the phase of starting a family, are discussed.
Online veröffentlicht: 11 Feb 2014
Gesehen am 05.05.2023